Recent Advances in Underwater Signal Processing - Sun, Haixin; Zhang, Xuebo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Seventy-one percent of the Earth is covered by oceans, which plays an important role in human life (ecological regulation, living resources, mineral resources, etc.). Underwater equipment including sonar and radar can help us to better understand the ocean. Using these technologies, topography, underwater communication, target detection, localization, imaging, and ocean monitoring can be easily carried out. Signal processing and electronics techniques have achieved great progress in recent years. Thanks to these developments, the novel theories, mechanisms, and processing techniques of underwater equipment have also been pushed into a new era. This Special Issue aims to highlight recent advancements, developments, and applications in underwater signal processing methodologies including characterization, simulation, real data processing, as well as applications to underwater engineering. In general, any contributions related to underwater signal processing or ocean signal processing will be considered.